2021
DOI: 10.1186/s12985-021-01619-8
|View full text |Cite
|
Sign up to set email alerts
|

Lineage analysis of human papillomavirus type 39 in cervical samples of Iranian women

Abstract: Background The data with regards to the regional variants of distinct HPV types is of great value. Accordance with this, this study aimed to investigate the sequence variations of E6 gene and long control region of HPV 39 among normal, premalignant and malignant cervical samples in order to characterize the frequent HPV 39 variants circulating in Tehran, Iran. Methods In total, 70 cervical samples (45 normal, 16 premalignant, and 9 malignant sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…Regarding the finding that lineage A of HPV 52 is prevalent in Iran, the E6 variation sequence analysis of other HPV types including HPV 16, 18, 31, 39, 45, and 56 in Iranian women showed that distinctive lineage/sublineages are dominant in this population as follows: for HPV 16 (lineage D), HPV 18 (sublineage A4), HPV 31 (lineage A), HPV 39 (sublineage A1), HPV 45 (lineage B), and HPV 56 (lineage B). 15 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the finding that lineage A of HPV 52 is prevalent in Iran, the E6 variation sequence analysis of other HPV types including HPV 16, 18, 31, 39, 45, and 56 in Iranian women showed that distinctive lineage/sublineages are dominant in this population as follows: for HPV 16 (lineage D), HPV 18 (sublineage A4), HPV 31 (lineage A), HPV 39 (sublineage A1), HPV 45 (lineage B), and HPV 56 (lineage B). 15 , 18 , 19 , 20 , 21 …”
Section: Discussionmentioning
confidence: 99%
“…Although the distribution of HPV types is well‐known in Iran, 11 there is much less identified about HPV lineages and sublineages in this country 15,18–21 . The data in this regard is important as it would provide a rationale for future studies on their epidemiology, evolution, pathogenicity, and biology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some types are supposed to have existed in specific regions although it seems traveling, tourism, and social communications increase the exposure risk of HPVs' different genotypes. Therefore, the various HPV genotypes were cocirculated between the communalities 6,8,10,19,25,45,[47][48][49][50][51][52][53]. Moreover, synergistic effects and trends in cocirculation of specific HPV genotypes are needed to be appraised in a future meta-analysis study.…”
mentioning
confidence: 99%